Digital watermarking and data hiding techniques - Zeki. Khedher, Akram M. (2006)
Watermarking is a special case of the general information hiding problem. The central idea is to robustly embed information in a medium known as the cover object in order to produce the stego object. The embedding is done in such a way that the cover and stego objects are indistinguishable